Pendampingan dan Penyuluhan Aspek Sosiopreneurship KWT Dahlia Desa Prawatan, Jogonalan, Klaten, Jawa Tengah - Erna Wati; Moh. Abdul Kholik; Sugiyanto Sugiyanto; Ambyah Atas Aji; Endra Yuliawan; Hendri Noviyanto (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2024)
Sociopreneurship is an effort to build a business or business with the main aim of achieving a positive social impact. This approach does not only focus on financial profits, but also pays attention to social welfare, improving people's living standards, and inclusive economic development. The targets of this community service activity are members of the Dahlia Women's Farmers Group (KWT) management and 30 village government officials in Prawatan Village. This activity was also attended by the Head of Prawatan Village, Agricultural PPL and also Community Figures. The counseling and mentoring activities were carried out for 150 minutes, divided into 4 sessions and continued with questions and answers. The first session presented economic material which discussed Cost of Goods Sold (HPP), the second session discussed cultivation and processing of feed waste, the third session discussed innovation and marketing technology for harvests, the fourth session discussed leadership and community group management, and the final session question and answer between the audience and the community service team